Hierarchy Analysis of Growth Center in DIY Coastal Area: Analisis Hirarki Pusat Pertumbuhan di Kawasan Pesisir DIY - yusliana; Devi, Mutiasari Kurnia (ReTII, 2019)
The southern coastal region of DIY is one of the Strategic Areas of the Province of DIY. Various efforts from the government to develop the region into a gateway to the DIY economy include building an international-scale airport in Wates Subdistrict and the construction of the Southern Cross Road that passes through all sub-districts located in the DIY coastal area is expected to trigger the emergence of new activities so as to form centers growth center. The purpose of this study is to determine the hierarchy of growth centers in the DIY Coastal region. The approach used is a descriptive quantitative approach with the analysis technique used is a scalogram analysis and centrality index analysis of the analysis it is known that the Primary Growth Center is in the District of Wates, the Secondary Growth Center is in the Kretek District and the Tertiary Growth Center is in the Saptosari Congestion. With the knowledge of the hierarchy in the coastal area it is hoped that development can remain the target.